Analisis Kelayakan Usahatani Jeruk Siam (Citrus nobilis Var Microcarpa) - Fauzi, Fadhillah Nur; Ginting, Nina Maksimiliana; Nurliah, Nurliah (Musamus University, 2024)
Analyzing production costs, income and survival of Siamese orange farming is the aim of this research. Telaga Sari Village was deliberately chosen for this research because it is one of the main producing areas of Siamese oranges in Kurik District, Merauke Regency. The sample size was 56 respondents grouped based on the age of Siamese orange plants, obtained using census sampling techniques. Qualitative and quantitative descriptive methodologies were used in data analysis. Production costs are IDR 22,505,313.70 for plants aged <5 years, IDR 54,497,518.63 for plants aged 6-10 years, and IDR 63,580,349.36 for plants aged >10 years. For plants aged <5 years, revenue is IDR 74,639,696.97; plants 6-10 years IDR 376,390,476.19; and >10 years IDR 498,000,000.00. Plants <5 years old, income of IDR 52,134,383.27; those who have 6-10 years old plants earn IDR 321,892,957.56; and those whose plants are >10 years old earn income of IDR 434,419,650.64. Based on the R/C Ratio analysis, the viability of Siamese orange farming is 3.32 for plants <5 years old, 6.91 for 6–10 years old, and 7.83 for >10 years old. Therefore, Siamese orange cultivation in Telaga Sari Village is worthy of development.